First record of total albinism in Molossus molossus (Chiroptera: Molossidae) from northeastern Brazil - do Nascimento, Andreza Cristina Soeiro; Moreira Dourado, Ângelo Cortez; Trevelin, Leonardo Carreira; Bezerra, Alexandra Maria Ramos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
Albinism is a condition caused by deletion of genes responsible for melanin production, resulting in the total absence of pigments. This genetic disorder is rare in nature and is known from ten Brazilian bat species, among them Molossus molossus. Here we report the first occurrence of this condition in M. molossus from northeastern Brazil. Since albinism is uncommon, it is important to report cases like this one, providing addicional data to understand albinism in bats andreinforce the importance of museum specimens as source of biological knowledge
Keywords: Bats; Genetic disease; Maranhão; Mutation; Hypopigmentation